World Prosperity and the British Balance of Payments - Hinshaw, Randall; Metzler, Lloyd A. (The Review of Economics and Statistics, 1945)
THROUGHOUT the inter-war period, the 1 value of commodity imports into the United Kingdom was consistently greater than the value of exports. In the fifteen-year period 1924 through 1938, the average annual commodity import surplus was 358 million pounds sterling. Payment for this import surplus was made in three ways. First, the British earned a substantial net income on their overseas investments; average annual receipts from this source in the fifteen-year period amounted to 209 million pounds sterling. Second, average annual net receipts of I04 million pounds sterling were obtained from the sale of shipping services to foreigners. Finally, the United Kingdom received income from abroad, in the form of interest and commissions, for its services as a financial center; the average amount of these receipts was 46 million pounds per year. Considering the inter-war period as a whole, the United Kingdom was able to pay for its commodity import surplus without resort to borrowing or to the sale of overseas assets. The import surplus was offset by invisible exports shipping and financial services and by income from overseas investments. This balanced position for the period as a whole, however, conceals a gradual deterioration in the British balance of payments on current account. In the earlier years (I924-30), invisible exports plus income from overseas investment were slightly greater than the commodity import surplus, but in the thirties (193I-38) the import surplus exceeded invisible income (Table I). Other items, of course, were included in the balance of payments, but in most years these were of minor importance. Changes in the British international position may therefore be described in terms of exports, imports, income from overseas investments, shipping income, and interest and commissions.